2020
DOI: 10.1111/dth.13883
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient dermatology consultations during COVID 19 pandemic in a tertiary referral center

Abstract: Since the COVID‐19 infection first appeared in December 2019, patient profile of outpatient and inpatient clinics have changed. Various cutaneous findings associated with COVID‐19 have been reported in the literature. The main objective of this study was to describe and analyze the profile of the consultations requested from dermatology department during the COVID pandemic. Retrospective, cohort study In this study we observed the dermatology consultations of the hospitalized patients over a period of 2 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 8 publications
2
8
0
Order By: Relevance
“…The COVID-19 pandemic has led to a significant decrease of paediatric dermatology consultations [ 17 ] and HRQoL in patients with skin diseases was found to worsen significantly compared to prepandemic studies [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic has led to a significant decrease of paediatric dermatology consultations [ 17 ] and HRQoL in patients with skin diseases was found to worsen significantly compared to prepandemic studies [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is more prevalent in adolescents and may be associated with postural orthostatic tachycardia syndrome (POTS) and other forms of orthostatic intolerance (OI). [1][2][3][4] We report two new cases of BASCULE syndrome in adolescent males emphasising its frequency in this age group and its possible association with disorders of the autonomic nervous system. A healthy, 13-year-old boy presented with a 6-month history of a bluish discoloration of his lower limbs associated with cramps and trembling.…”
Section: Case Lettermentioning
confidence: 99%
“…1 As such the experience of dermatology departments in Australia has differed from those reported in Europe and the United States. 2 , 3 , 4 , 5 , 6 …”
Section: Figurementioning
confidence: 99%
“…Taken in their totality, we see that due to the multi-system effects of COVID-19, a multidisciplinary approach is often needed in order to optimize care. In fact, COVID-19 patients can make up a significant portion of inpatient dermatology consults – one study found that over 30% of dermatology consults at a tertiary care hospital were for COVID-19 patients and over 40% of all dermatology consults were done via telemedicine ( Trinidad et al, 2020 ; Uzuncakmak et al, 2020 ; Bhargava et al, 2021a ).…”
Section: Id Perspectivesmentioning
confidence: 99%